Red foxes (Vulpes vulpes) and raccoon dogs (Nyctereutes procyonoides) as potential spreaders of Sarcocystis species - Máca, Ondřej; Gudiškis, Naglis; Butkauskas, Dalius; González-Solís, David; Prakas, Petras (Frontiers in Veterinary Science, 2024)
Background Sarcocystis includes a global group of apicomplexan parasites with two-host life cycle frequently circulating in wildlife and domestic hosts, including humans. Two of the most important wild terrestrial carnivores acting as definitive hosts are the red fox and raccoon dog, due to their wide distribution in Europe and usage of wild and farmed animals as prey. This study was conducted to determine the prevalence of Sarcocystis in hunted red foxes and raccoon dogs from nine regions of the Czech Republic and to identify isolated sporocysts by molecular techniques. Methods Approximately 5 g of the contents of large intestine from 200 animals (197 red foxes and three raccoon dogs) were examined by flotation centrifugation coprological method. Only samples of 50 red foxes and one raccoon dog positive to Sarcocystis spp. were used for the nested PCR (nPCR) method to amplify a fragment or partial sequence on the cox1 gene. Ten species-specific primer pairs for detection of Sarcocystis spp. using farm animals as intermediate hosts were utilized. Results In total, 38.1% of the red foxes and 66.7% of the raccoon dogs were positive to Sarcocystis by light microscopy. The molecular characterization resulted in the identification of five species in the red fox: S. arieticanis, S. capracanis, S. cruzi, S. miescheriana, and S. tenella, while the PCR was negative for the sole raccoon dog. The highest intraspecific variation was found for S. miescheriana, while S. tenella was the most prevalent. Co-infections occurred in the large intestine of the red fox. No zoonotic species were found in our samples. Conclusion This is the first study where the potential role of the red fox and raccoon dogs as spreaders of Sarcocystis to farm animals in the Czech Republic is shown. The use of species-specific primers provides a fast and easy method for screening multiple samples for a particular Sarcocystis species.